Respuesta :
Answer:
f(3)=2(3)^2+4
f(3)=2(9)+4
f(3)=18+4
f(3)=22
Step-by-step explanation:
In this scenario, x=3 so you plug it into the other side of the equation.
ANSWER
[tex]f(3) = 22[/tex]
EXPLANATION
The given given function is
[tex]f(x) = 2 {x}^{2} + 4[/tex]
To find f(3), we substitite x=3 into the function f(x).
This means that wherever we see x in
[tex]f(x) = 2 {x}^{2} + 4[/tex]
we replace it with 3 .
[tex] \implies \: f(3) = 2 ({3})^{2} + 4[/tex]
We evaluate the square to get:
[tex] \implies \: f(3) = 2 ({9}) + 4[/tex]
Perform the multiplication
[tex] \implies \: f(3) = 18 + 4[/tex]
Now add to get:
[tex] \implies \: f(3) = 2 2[/tex]